Localization of TGF-β3 in intra bony defect treated by local application of chitosan β- TCP in rabbits - Almashhadi, Zainab AJ; Al-Ghaban, Nada MH (Journal of Baghdad College of Dentistry, 2025)
Background: Bone defect is a lack of bone tissue continuity, bone defects may be caused by trauma, tumor, or infection. The aim of study to evaluate the expression transforming growth factor beta three (TGF-β3) in intra bony defects treated with chitosan and beta tricalcium phosphate and their combination. Materials and methods: A total of thirty two male New Zealand rabbits were weighed about(1.5-2kg) assigned randomly into four groups, each rabbits received bilateral defect in each femur, these bony defects were divided into four groups: Control group (8 bony defects): these bony defect were left to heal normally without treatment, chitosan hydrogel group (8 bony defects), beta tricalcium phosphate group (β-TCP): (8 bony defects , Combination group (8) bony defects): these bony defects were treated with both of chitosan hydrogel and β-TCP powder . All animals had been sacrificed after 2,4 weeks and the specimens were processed routinely for a serial decalcified sections for the immunohistochemical study on TGF-β3. Result: The immunohistochemical findings had shown a higher immunoreactivity of the bone cells of the experimental group than the control groups. Conclusion: The study revealed that local application of chitosan hydrogel and their combination with TCP accelerate bone formation by increased the expression of TGFβ3 in intra bony defect more than that in normal physiological process.